2023
DOI: 10.1002/jcsm.13306
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and heart failure: State‐of‐the‐art review

Khawaja M. Talha,
Ambarish Pandey,
Marat Fudim
et al.

Abstract: At least half of all patients with heart failure (HF) are affected by frailty, a syndrome that limits an individual ability to recover from acute stressors. While frailty affects up to 90% of patients with HF with preserved ejection fraction, it is also seen in ~30–60% of patients with HF with reduced ejection fraction, with ~26% higher prevalence in women compared with men. The relationship between frailty and HF is bidirectional, with both conditions exacerbating the other. Frailty is further complicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 103 publications
(202 reference statements)
0
16
0
Order By: Relevance
“…Heart failure patients with sarcopenia and frailty are known to have a higher mortality. 10 Measures of frailty can be cumbersome to perform in the clinical setting. Similarly, measures of sarcopenia typically require additional imaging, incurring extra costs for patients in terms of both time and finances.…”
mentioning
confidence: 99%
“…Heart failure patients with sarcopenia and frailty are known to have a higher mortality. 10 Measures of frailty can be cumbersome to perform in the clinical setting. Similarly, measures of sarcopenia typically require additional imaging, incurring extra costs for patients in terms of both time and finances.…”
mentioning
confidence: 99%
“…The impact of frailty on patient outcomes was investigated across various cardiovascular conditions. Among patients with heart failure (HF), frailty is more common than in the general papulation, with a reported prevalence of 21-80% [7][8][9]. Prevalence is higher among women, as well as in patients with HF with preserved ejection fraction, relative to those with reduced ejection fraction [8].…”
mentioning
confidence: 99%
“…Among patients with heart failure (HF), frailty is more common than in the general papulation, with a reported prevalence of 21-80% [7][8][9]. Prevalence is higher among women, as well as in patients with HF with preserved ejection fraction, relative to those with reduced ejection fraction [8]. Frailty constitutes an independent risk factor for mortality and hospitalizations related to HF, and it was demonstrated that adding frailty assessment to HF risk scores improves the discrimination ability for future death and HF hospitalizations [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations